Cleaving : a story of marriage, meat, and obsession - Powell, Julie (New York : Little, Brown, 2009)
The popular blogger describes how in the wake of a strain on her marriage she left town to immerse herself in the art of butchery, the laborious training she received, and her journeys throughout the world in search of the butchery practices of other cultures.
Keywords: Powell, Julie; Powell, Julie -- Marriage; Women cooks -- New York (State) -- New York -- Biography; Cooks -- New York (State) -- New York -- Biography; Butchers -- New York (State) -- Kingston -- Biography; Meat cutting -- Psychological aspects; Fleisher's (Kingston, N.Y.); New York (N.Y.) -- Biography; Kingston (N.Y.) -- Biography